The Effect of Technological Parameters on the Foaming of Injection Molded, Recycled PET - Molnar, B. (Acta Technica Jaurinensis, 2014)
The foaming of regranulate made from recycled PET bottles was examined, varying two important technological parameters: holding pressure, and the amount of material injected into the mold cavity, which was controlled with the switchover point. It was shown with optical and density tests that these parameters have a significant effect on the foam structure, which greatly influences mechanical properties.